EVALUATION OF THE QUALITY OF TREATMENT DESTRUCTIVE FORMS OF CHRONIC APICAL PERIODONTITIS - A. V. Arutyunov; V. I. Starchenko; A. A. Ovsyannikova; A. B. Larina; N. I. Bykova (Кубанский научный медицинский вестник, 2016)
Article is devoted to clinicoradiological evaluation of quality of endodontic treatment of destructive forms of chronic apical periodontitis as a result of the application of the material for filling root canals in the treatment of granulomatous and granulating forms of chronic periodontitis. This material was used in the treatment of 86 teeth in 46 patients aged 18-65 years in clinic. It was established that the material is allowed to reliably obturated root canal, to stop inflammation in the periodontal stimulate repair processes in the periapical tissues. This has been confirmed in long-term period on the basis of X-ray cone beam computed tomography in accordance with the scale of Hounsfield. The first radiographic appearance of the beginning of reparative regeneration of bone tissue in the main group appeared on 32,8±0,5 days. The same factors appeared on 49,7±0,4 days in control group. Bone defect restoration around the hearth of destruction in the main group took, on average, 64,8±0,5, against 98,7±0,3 days in the control group. Methods of cone beam computed tomography allows the remote period after endodontic treatment to dynamically control the state of the bone-destructive foci of chronic apical periodontitis (granulating and granulomatous pathological forms) and define the rate of regeneration of bone tissue. It allows you to objectively evaluate the degree of bone regeneration in the destruction of the hearth.